Investigating team teaching through an exploration of beliefs about role and effective teaching : a case study of New Zealand and Thai primary teachers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Second Language Teaching at Massey University - Ashdown, Lucette Margaret (Massey University, 2002)
This case study investigates the nature of team teaching relationships from the viewpoint of Thai and New Zealand teachers working in bilingual primary level classrooms. Team relationships were explored through investigating expectations and assumptions teachers had about effective teaching, and how these impacted on classroom roles, relationships and teaching practices. There were six subjects who participated in the study; three Thai and three New Zealand teachers. Data was collected over a period of five months. Primary data was gathered using classroom observations, guided and informal interviews. Secondary data, gathered from a biodata questionnaire, stimulated recall using a videotaped classroom observation and informal observations, was used to confirm and expand findings from the primary sources. The study found that team teaching is both a structural arrangement and an emergent process. The way in which teams develop is related to the relationship built by participants. A number of variables were found to influence the direction of team relationships: time, trust and professional respect, communication, personality, and beliefs about teaching and learning. Teams developed either autonomously or collaboratively depending on how participants negotiated these variables.
Keywords: Thailand; Foreign speakers; English language; Teaching teams; Study and teaching